KEPEMIMPINAN CAMAT DALAM PELAKSANAAN URUSAN PEMERINTAHAN UMUM DI KECAMATAN SINGKEP SELATAN KABUPATEN LINGGA PROVINSI KEPULAUAN RIAU TAHUN 2019 - Muswanto Aldi Pratama Jeremias; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The subdistrict head is the leader of the sub-district, this is in accordance with Article 1 of Government Regulation Number 17 of 2018 concerning the District. One of the things that must be carried out by the sub-district head is to carry out general government affairs as regulated in paragraph (6) Article 25 of Law Number 23 of 2014 concerning Regional Government. Thus, the Head of South Singkep Sub-District, Lingga Regency, Riau Islands Province must also carry out these obligations, in addition to other duties. The formulation of the research problem: how is the sub-district leadership in the implementation of general government affairs in Singkep Selatan District, Lingga Regency, Riau Islands Province in 2019? What are the factors that hinder the head of the sub-district leadership in implementing general government affairs in Singkep Selatan District Lingga Regency Riau Islands Province in 201? The research objectives are: to determine the leadership of the sub-district head in the implementation of general government affairs in Singkep Selatan District, Lingga Regency, Riau Islands Province in 2019, to find out what factors are hindering the sub-district leadership in implementing general government affairs in Singkep Selatan District Lingga Regency Riau Islands Province in 2019 .The leadership of the sub-district head in the implementation of general government affairs in Singkep Selatan District, Lingga Regency, Riau Islands Province in 2019 by: conveying the contents of general government affairs verbally, providing support for the availability of facilities and infrastructure and organizing activities, coordinating with the District Leadership Communication Forum (FORKOMPIMKA). The factors that hinder implementation are the funding factor and the time limitation factor for the camat. Keywords: Contents of general government affairs orally, support for the availability of facilities and infrastructure, FORKOMPIMKA